A Case of Spontaneously Improving Secondary Hemophagocytic Lymphohistiocytosis in an Adult Associated with T-Cell Histiocyte-Rich Large B-Cell Lymphoma - Cyrus Askin; Ashley Burris; Clifton Layman; Brian Haney; Jordan Hall (Case Reports in Oncological Medicine)
Secondary hemophagocytic lymphohistiocytosis (HLH) in adults is a rare, often fatal syndrome characterized by widespread immune dysregulation. It is seen as a complication of infections, autoimmune diseases, and malignancies. Among the malignancy-related causes, aggressive T-cell or NK-cell neoplasms are most notable, while B-cell lymphomas are less commonly implicated. We present the case of a 32-year-old male transferred to our facility with concern for HLH. During the first week of his hospitalization, his diagnosis was confirmed and the patient demonstrated spontaneous improvement in his symptoms prompting us to delay therapy while searching for a primary cause. In the second week, the patient deteriorated, leading us to initiate steroid monotherapy in the absence of a cause for his HLH. Meanwhile, pathology results from an excisional lymph node biopsy confirmed a diagnosis of T-cell/histiocyte-rich large B-cell lymphoma (TCHRLBCL). Subsequently, we initiated therapy with dose-adjusted R-EPOCH. The patient achieved a complete remission of both HLH and TCHRLBCL as well as a complete return to his prior functional status. In our review of the literature, this represents only the second documented case of HLH associated with TCHRLBCL and the only documented case of an adult experiencing significant spontaneous recovery in this context.